Method to evaluate states of concentration, using brain-computer interface, in online mathematics classes - Pando Ezcurra, Tamara (2022)
Online classes are causing many changes, from the behavior of students to the way they are understanding the classes. In a normal situation, students are in school classrooms, where the environment is suitable for students to pay the most attention, in these times, where online classes are developed, classes are developed at home, where they were adapted environments to carry out these activities, in these situations they cause the appearance of distracting agents, causing students to be distracted when they are in class, these distracting agents can be the same house, the toys, the television and in some cases the brother who is in classes and found in the same environment. The proposed methodology proposes the analysis of the environment where the online classes are held, in a particular case, with the use of the BCI device, measurements of concentration and meditation levels are carried out, on a scale from 0% to 100 %, measurements are carried out in various conventional situations that are carried out in class, with the intention of being able to determine the best strategies so that students can have the best concentration when taking mathematics classes; The results determine that in a conventional situation the student has a concentration level of 20%, which indicates that he is not very attentive to the classes, but when we try to eliminate most of the distracting agents and concentrating on the class, we achieve a level of attention that reaches 90 ”with minimum values of meditation, which indicates that the students can achieve better concentration in the classes, in order to take advantage of the class and solve math problems, we finished the work recommending the best conditions that they must be presented in order to present high levels of attention when taking online classes.